The Effect of Servicescape on Customer Loyalty Through Consumer Satisfaction as an Intervenig Variable Study on Consumers of Alamanis Resort Villa Cirebon Village - Malik Rismanto; Kiflu Chekole Tekle; Ade Fitria Fatimah (Advances In Social Humanities Research, 2026)
The service industry, particularly the hospitality sector, plays an important role in supporting tourism development and economic growth. In the hotel and resort business, servicescape becomes a crucial factor in shaping customer experiences, satisfaction, and loyalty. Alamanis Resort Villa Cirebon Village offers a unique traditional environment concept that combines cultural elements and natural atmosphere to create memorable experiences for visitors. This study aims to describe between servicescape to customer loyalty and to analyze the indirect impact on consumers as an intervening variable on consumers in Desa Alamanis Resort Vila Cirebon Regency. The population is all visitors of Desa Alamanis Resort Vila Cirebon Regency by using associative research method. While the samples are consumers of Desa Alamanis Resort Vila Cirebon Regency as many as 100 respondents, using incidental sampling. The analysis used in this research is Path Analysis Method. The results showed that the servicecape variable to customer loyalty did not have a significant effect with proven by the value of t arithmetic smaller than t table that is 1.560 <t table 1.984. Meanwhile, servicescape indirectly affect consumer loyalty through consumer satisfaction, this is proven by the sobel test to know the magnitude of the mediation variables that is with t count larger with t table 3.864> t table 1.984. Thus, indirectly servicescape variables have an influence on customer loyalty through customer satisfaction as intervening variables.